A longitudinal study of backcountry track and campsite conditions on the Overland Track, Tasmania, Australia. (September 2017) - Dixon, Grant
Abstract: The 79 km Overland Track is Tasmania's premier overnight walking track (trail) and one of Australia's best-known and most popular backcountry hikes. Trampling impacts (poor track condition) were recognised in the 1970s and degraded campsites were a concern by the 1980s. Despite three decades of intermittent works, many sections of track remained in poor condition in the early 2000s, but targeted works since 2006 have addressed many problem areas. Hardening of campsites at selected overnight nodes commenced in 2000 and a reduction in overall camping impacts followed, presumed due to a greater concentration of camping use at the hardened sites despite unrestricted camping still being permitted. Longitudinal monitoring of both track (8 years) and campsite (16–25 years) conditions, using relatively simple techniques, have successfully described the scale and delineated the location of changes in condition and so provided a useful planning tool for management. In particular, it has contributed to documenting a contemporaneous improvement in track and campsite conditions partly associated with a booking system to regulate walker use of the Overland Track, introduced in 2005. Booking fees have contributed to management successes by providing adequate and consistent resourcing for the repair and maintenance of walking track surface infrastructure. Management implications: Extensive hardening is an effective way to sustainably manage a moderate to high use walking track that has not been initially well-designed. Adequate and consistent resourcing for the repair and maintenance of walking track surface infrastructure is necessary to sustainably manage such tracks. The provision of inviting facilities, including camping platforms, at selected overnight nodes has resulted in a concentration of visitor camping use on a smaller number of campsites, hence reducing the overall impact of camping along the Overland Track.